An investigation of the switching behavior and why customers switch banks in the retailing banking sector - Batmunkh, Ganshagai (Frontiers in Communication, 2025)
The systematic review looks at the elements that influence consumer switching behavior in the retail banking industry, which includes fintech companies, online platforms, and traditional banks. Financial institutions must concentrate on pricing tactics, service quality, and cutting-edge product offerings in a competitive market to keep clients. Key factors influencing consumer switching behavior, including service quality, pricing competitiveness, digital banking capabilities, and customer satisfaction, are identified in this study through a systematic literature review (SLR) of six chosen papers published between 2020 and 2024. It also draws attention to retention obstacles like subpar customer service and a lack of alignment with customer values. The study suggests methods for lowering customer attrition in order to address these issues, such as raising service standards, cutting banking costs, enhancing digital products, and matching customer expectations. This review identifies gaps in the literature and provides retail banks with actionable suggestions to reduce attrition and enhance customer loyalty by combining insights from various geographic contexts. For financial institutions looking to adjust to changing customer preferences and cultivate enduring partnerships in the retail banking sector, the findings offer insightful advice.